Gestión de logística y su incidencia en la red de mercados de los comerciantes minoristas del gobierno autónomo descentralizado municipal del cantón Echeandía año 2022 - Escudero Sánchez, Franklin Patricio (2022)
Logistics management has gained relevant importance in all areas of society, since it allows efficient management of all operations that seek to produce a good or service, or guarantee the availability of a certain element; product, information in optimal time and form; It is increasingly important to have procedures that allow having an adequate organization of resources, both in time and space, the objective was to evaluate the incidence of logistics management in a network of markets of retailers of the Municipal Autonomous Decentralized Government of the Echeandía canton, for this purpose is mainly based on field research, which once different types of informants have been defined, allow the collection of significant data, which have been used to propose an alternative solution. As results, the need to organize the retail markets in such a way that they do not affect the merchants of the municipal market is evident, for which a possible ordinance is proposed that regulates these services and that supports the GAD of the Echeandía canton, both logistically and economically. . Finally, it is determined that there is an exponential increase in informal merchants, which makes it necessary to make timely decisions about their organization and control, in such a way as to regulate and control this growth, for the benefit of citizens and the canton in general.